2021
DOI: 10.1016/j.tranon.2021.101077
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal alternative splicing promotes tumor resistance in targeted therapy and immunotherapy

Abstract: Highlights Abnormal alternative splicing is involve in abnormal expression of genes in cancer. Abnormal alternative splicing events promote malignant progression of cancer. Abnormal alternative splicing develops tumor resistance to targeted therapy by changing the target point and signal transduction pathway. Abnormal alternative splicing develops tumor resistance to immunotherapy by changing cell surface antigens and protein structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 95 publications
0
13
0
Order By: Relevance
“…As a result of this, the CD19 antigen is unable to properly adhere to the cell surface [ 155 ]. Deng et al showed that malignant B cells that express CD19 transcripts without exon 2 had reduced SRS3 gene expression [ 156 ]. The SRS3 gene (locus 6p21.31-p21.2) encodes a splicing factor that affects pre-mRNA processing and is involved in the recognition of terminal exons [ 157 , 158 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a result of this, the CD19 antigen is unable to properly adhere to the cell surface [ 155 ]. Deng et al showed that malignant B cells that express CD19 transcripts without exon 2 had reduced SRS3 gene expression [ 156 ]. The SRS3 gene (locus 6p21.31-p21.2) encodes a splicing factor that affects pre-mRNA processing and is involved in the recognition of terminal exons [ 157 , 158 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among proteins with an important role in the alternative splicing processes, we can highlight the significantly upregulated SNRPB2, SNRNP70 and SNRPA1 proteins [ 90 ] (GO Biological Process, FDR < 0.05) ( Figure S4 ) ( Figure 6 2D). Studies have confirmed that the abnormal expression of the splicing proteins can lead to inappropriate splicing mechanisms, causing tumor progression [ 91 ]. Denga et al also suggested that these disordered splicing mechanisms could promote the loss of cell surface antigens, which are crucial in melanoma and immune cell fusion that might contribute to immunotherapy resistance [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have confirmed that the abnormal expression of the splicing proteins can lead to inappropriate splicing mechanisms, causing tumor progression [ 91 ]. Denga et al also suggested that these disordered splicing mechanisms could promote the loss of cell surface antigens, which are crucial in melanoma and immune cell fusion that might contribute to immunotherapy resistance [ 91 ]. In the clinical field, the anti-spliceosome therapies are currently debated in their application of spliceosome machinery targeting [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, these samples of explanation give us insights into how alternative splicing is altered at different levels in cancers. Adding to the complexity, this mechanism has also been described as implicated in various chemoresistance mechanisms ( 87 89 ) (not detailed here). Therefore, RNA splicing modulation is, without a doubt, a crucial element to consider in the development of new therapeutic strategies to prevent, ameliorate treatment efficiency, and fight cancer.…”
Section: Rna Splicing and Cancermentioning
confidence: 98%